Genetic gains in grain yield under nitrogen stress following three decades of breeding for drought tolerance and Striga resistance in early maturing maize - Badu-Apraku, Baffour; Fakorede, M.A.B.; Oyekunle, M.; Akinwale, R. (Cambridge University Press, 2016)
Breeding for resistance to Striga hermonthica Del. (Benth) and tolerance to drought has been a major strategy to improve maize (Zea mays L.) production and productivity in West and Central Africa during the last three decades. The three decades consisted of three breeding periods or eras based on the germplasm and methodologies used; that is, 1988–2000, 2001–06 and 2007–11. A total of 50 early maturing cultivars, combining Striga resistance with drought tolerance were developed, including 15, 16 and 19 cultivars for the three periods, respectively. Although the cultivars were not selected intentionally for low-nitrogen (N) tolerance, it was hypothesized that tolerance to low-N had been significantly improved while selecting for drought tolerance and Striga resistance. This hypothesis was tested by evaluating the 50 cultivars in 2010 and 2011 in Nigeria at Mokwa and Ile-Ife under both low-N (30 kg N/ha) and high-N (90 kg N/ha) levels. Under low-N conditions, grain yield improved from 2280 kg/ha during the first period to 2610 kg/ha during the third period, an increase of 165 kg/ha per period with r2 of 0·99. Under high-N, yield increased from 3200 to 3650 kg/ha, an increase of 225 kg/ha and r2 of 0·93. Relative gain per period was 30 kg/ha for the two N rates with r2 values of 0·99 and 0·94 respectively. Grain yield performance of the 50 cultivars under low-N conditions adequately predicted their performance under high-N. Selection for Striga resistance and drought tolerance in early maturing maize populations enhanced low-N tolerance in the maize cultivars derived from the populations. The improvement was higher in later than earlier breeding periods.